To complete the square for the quadratic equation x^2 - 6x - 20 = 20, we need to add and subtract the square of half the coefficient of x.
First, let's move the constant term to the right side of the equation:
x^2 - 6x = 20 + 20
x^2 - 6x = 40
Next, take half of the coefficient of x, which is -6, and square it:
(-6/2)^2 = (-3)^2 = 9
Now, add and subtract 9 to the left side of the equation:
x^2 - 6x + 9 - 9 = 40
(x^2 - 6x + 9) - 9 = 40
(x - 3)^2 - 9 = 40
Now, we can simplify the equation:
(x - 3)^2 = 40 + 9
(x - 3)^2 = 49
Taking the square root of both sides:
x - 3 = ±√49
x - 3 = ±7
Now, solving for x:
x = 3 + 7 = 10
x = 3 - 7 = -4
Therefore, the solutions to the quadratic equation x^2 - 6x - 20 = 20 are x = 10 and x = -4.
omplete the square to solve the following quadratic equation: x2−6x−20=20%0D%0A%0D%0A2%0D%0A−%0D%0A6%0D%0A%0D%0A−%0D%0A20%0D%0A=%0D%0A20%0D%0A .(1 point)
1 answer